2009
DOI: 10.3329/bjmm.v3i1.2969
|View full text |Cite
|
Sign up to set email alerts
|

Nosocomial Multi-Drug-Resistant Acinetobacter Infections - Clinical Findings, Risk Factors and Demographic Characteristics

Abstract: Recently, Acinetobacter emerged as an important pathogen and the rate of isolation has increased since the last two decades worldwide. Objectives of the present study were to see the incidence of Acinetobacter infection at a tertiary care hospital at Kashmir, India, demographic features of the infections, species identification and antibiotic sensitivity and resistance pattern of the isolates. The clinical samples submitted to Microbiology laboratory at SKIMS over a period of 2 years (June, 2001 to June, 2003)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
27
2

Year Published

2012
2012
2018
2018

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(36 citation statements)
references
References 16 publications
7
27
2
Order By: Relevance
“…In present study, Acinetobacter accounted for359 (34.5%) of total positive culture, 176 (49%) of non-fermenter, 88 (50%) of non-motile and 2.8% of total samples cultures. The present study is supported by previously, published studies which have accounted 12.9% (Lahiri et al, 2004) and 4.8% (Lone et al, 2009) of Acinetobacter isolates from total infected samples, respectively. …”
Section: Resultssupporting
confidence: 81%
See 1 more Smart Citation
“…In present study, Acinetobacter accounted for359 (34.5%) of total positive culture, 176 (49%) of non-fermenter, 88 (50%) of non-motile and 2.8% of total samples cultures. The present study is supported by previously, published studies which have accounted 12.9% (Lahiri et al, 2004) and 4.8% (Lone et al, 2009) of Acinetobacter isolates from total infected samples, respectively. …”
Section: Resultssupporting
confidence: 81%
“…It is very much necessary to know about the alteration in Acinetobacter resistogram, for a periodic observation of these pathogens to get suitable group of treatment (Prashanth et al, 2004 andLone et al, 2009) Due to random antibiotic resistance patterns of clinical strains of Acinetobacter, it is necessary to know the institutional widespread susceptibility profiles of this pathogen. In India a small number of studies on Acinetobacter species have been reported especially in Uttar Pradesh and in analysis of their increasing significance in nosocomial infections, more study is needed in this part.…”
mentioning
confidence: 99%
“…infections were age ≥50 years, length of stay in hospital, invasive procedures like catheterization, intubation, and mechanical ventilation with underlying comorbid conditions such as diabetes mellitus, similar to the findings of the studies published earlier [9,14,15].…”
Section: Discussionsupporting
confidence: 78%
“…Advanced age is a risk factor for acquiring infection with Acinetobacter species which could be attributed to the poor immune defense mechanisms in the elderly age group and the presence of coexisting comorbidities and chronic diseases. Other studies on infections with Acinetobacter species also reported male preponderance and increased incidence in older group [6,13].…”
Section: Discussionmentioning
confidence: 94%
“…Non-random sampling method was adopted for the study. The following variables were analyzed: ICU admission, duration of stay in the hospital, mechanical ventilation, endotracheal intubation, the presence of underlying diseases or conditions, including chronic obstructive pulmonary disease (COPD), diabetes mellitus, hypertension, chronic kidney disease (CKD), chronic liver disease, ischemic heart disease, malignancy, past history of device implantation or surgery, and instrumentation at various sites such as Central venous catheters [4][5][6][7]. Ventilator-associated pneumonia (VAP) is defined according to the American Thoracic Society as pneumonia that occurs 48-72 hrs or thereafter following endotracheal intubation, characterized by the presence of a new or progressive infiltrate, signs of systemic infection (fever, altered white blood cell count), changes in sputum characteristics, and detection of a causative agent [8].…”
Section: Methodsmentioning
confidence: 99%